1057 Evaluating Differences In Upper Airway Anatomy Between Diabetic And Non-diabetic OSA Patients. (27th May 2020) - Ihemeremadu, N; Lavi-Romer, N; Zang, Y; Keenan, B; Schwab, R
Abstract: Introduction: Studies show that OSA is linked to impaired glucose tolerance, insulin resistance, and the onset of diabetes. We hypothesized that diabetic OSA patients will have higher apnea-hypopnea index (AHI) values than OSA patients without diabetes after adjusting for age and body mass index (BMI) and that this difference can be explained through increases in upper airway structures between diabetic and non-diabetic OSA patients. Methods: This study evaluated differences in upper airway and craniofacial dimensions and volume of the pharyngeal soft tissues between diabetic and non-diabetic patients with obstructive sleep apnea (OSA) using magnetic resonance imaging (MRI). Airway sizes, soft tissue volumes and craniofacial dimensions were quantified using three-dimensional MRI in OSA patients without diabetes (n=237) and OSA patients with diabetes (n=64). Comparisons in upper airway measures among diabetics and non-diabetics were performed using linear regression models controlling for age, sex, BMI, race, and AHI. Results: Among study participants, diabetic OSA patients were older than non-diabetic OSA patients (54.2±10.1 vs. 47.3±11.1 years; p<0.0001). No significant differences were found between diabetic and non-diabetic OSA patients with respect to BMI (39.8±7.0 vs. 38.4±8.8 kg/m 2 ; p=0.207) or AHI (45.0±31.0 vs. 38.8±27.8 events/hour; p=0.154). In covariate adjusted models, non-diabetic OSA patients also had smaller RP minimum airway area (adjusted difference [95% CI] = -3119 [-5359, 879] mm 2 ; p=0.0066) and RP minimum AP distance (-16.0 mm [-29.6, -2.5]; p=0.021) compared to diabetic OSA patients. No differences were observed in soft tissue volumes or craniofacial dimensions. Conclusion: While diabetics had higher average AHI, we observed no significant differences in AHI between diabetic and non-diabetic patients with sleep apnea. In general, upper airway anatomy was similar between diabetic and non-diabetics apneics, controlling for demographic factors and AHI. Future studies should examine dynamic changes, in addition to static upper airway anatomy, in diabetic and non-diabetics apneics. Support: